E-Governance in Public Institutions: A Systematic Review of International Studies (2013 – 2024) - Nahal Mahmood , Yazen; Ali Mhaibes , Hussam; AL-Dunainawi, Yousif (Journal of Economics and Administrative Sciences, 2025)
This study aims to review and compare research related to E-governance in public institutions with the aim of identifying common denominators that increase or decrease its effectiveness and to evaluate the evaluation methods used. By highlighting the factors of success and failure, the study paves the way for future research and links theory to practice. The study question addresses how E-governance is applied differently and similarly in Arabic and foreign studies, in addition to the effects of variables and the methodology used. Our study follows PRISMA rules, ensures quality and transparency of selection, and conducts a comprehensive analysis of research published between 2013 and 2024 based on reliable data standards such as Google Scholar. We focused in both Arabic and English on studies related to E-governance in the administrative field. These initiatives seek to improve communication and transparency while significantly enhancing electronic innovation and access to government services. However, they face difficulties such as a lack of expertise in the field of cybersecurity, a lack of funding, and weak infrastructure. Despite its weak adoption in government institutions due to weak infrastructure, E-governance enhances access to government information services. As a result, it is necessary to revitalize government institutions by allocating sufficient funding for their growth and implementing plans, policies, and strategies that meet E-governance also significantly improves the timeliness of policy advisory functions, which also increases the effectiveness of sound policy implementation.